Survey data on e-Procurement adoption in the Nigerian building industry - Eziyi O. Ibem; Egidario B. Aduwo; Uwakonye O. Uwakonye; Patience F. Tunji-Olayeni; Emmanuel A. Ayo-Vaughan (Data in Brief, 2018)
This article is a description of data related to the research article entitled “Factors influencing e-Procurement adoption in the Nigerian Building Industry” (Ibem et al., 2016) [1]. The data were derived via a questionnaire survey involving 213 participants comprising architects, quantity surveyors, builders, construction/project managers, and engineers working in consulting and contracting firms, private client organisations and government agencies. The survey was conducted in Nigeria between June and November 2015. The data set contains responses on the levels of awareness and extent of use of the different e-Procurement technologies, the barriers to the uptake as well as the factors influencing e-Procurement adoption by organizations in the Nigerian building industry. The survey data and results of the analysis are made available in this article for further use by researchers; and for the purpose of improving understanding of the key findings of the survey. Keywords: e-Procurement, Building industry, Survey, Nigeria